A comparison of melancholic and nonmelancholic recurrent major depression in Han Chinese women. - Sun, N; Li, Y; Cai, Y; Chen, J; Shen, Y; Sun, J; Zhang, Z; Zhang, J; Wang, L; Guo, L; Yang, L; Qiang, L; et al. (2012)
BACKGROUND: Although the diagnosis of melancholia has had a long history, the validity of the current DSM-IV definition remains contentious. We report here the first detailed comparison of melancholic and nonmelancholic major depression (MD) in a Chinese population examining in particular whether these two forms of MD differ quantitatively or qualitatively. METHODS: DSM-IV criteria for melancholia were applied to 1,970 Han Chinese women with recurrent MD recruited from 53 provincial mental health centers and psychiatric departments of general medical hospitals in 41 cities. Statistical analyses, utilizing Student's t-tests and Pearson's χ(2) , were calculated using SPSS 13.0. RESULTS: Melancholic patients with MD were distinguished from nonmelancholic by being older, having a later age at onset, more episodes of illness and meeting more A criteria. They also had higher levels of neuroticism and rates of lifetime generalized anxiety disorder, panic disorder, and social and agoraphobia. They had significantly lower rates of childhood sexual abuse but did not differ on other stressful life events or rates of MD in their families. DISCUSSION: Consistent with most prior findings in European and US populations, we find that melancholia is a more clinically severe syndrome than nonmelancholic depression with higher rates of comorbidity. The evidence that it is a more "biological" or qualitatively distinct syndrome, however, is mixed.